O Pessach ontem e hoje - Burdelak, Cristiano Cesar (2013)
This paper is a bibliographical historical analysis of the theme Pessach yesterday and today . At the first moment, the Pessach will be detailed in its historical evolution showing the origins and practice of this celebration, presuming the influence of other peoples which reflected such customs, and thus proceeded from these origins, including other literature throughout history. Following this, some attributes of Pessach will be presented, being pointed out in a certain organization to preserve the continuity of this tradition, which was given to the Jewish people, in as much as these characteristics were added lending to new interpretations in the occasions of the moments with the circumstances of the environment. The central proposal are the typological analogies of the historical readings with the prophetic ones, where everything took place centered on the paschal lamb as the redemptive sacrifice. After the destruction of the second Temple, the Pessach begins to gain ressignifications, for the traditional Jews as well as for the Messianic Jews and the Christians, having prophetic fulfillment in various characteristics connected to this sphere. The goal of this paper is to seek to recover the knowledge of the times and thus understand why the lamb was not only for the Exodus but was for all times. Thus, the families would meditate, retrospectively, on their liberation (believed by the traditional Jews). The act, on the other hand, talked prospectively of a total liberation, which would emerge from the sacrificial death of the Lamb of Pessach (Yeshua Ha Mashiach, believed by the Messianic Jews and the Christians) which, taking place once in history, would originate the finished redemption, no longer necessitating any further spilling of blood of the paschal Lamb.